Effectiveness of case management in the prevention of COPD re-admissions: a pilot study. (December 2017) - Eeden, Annelies; Poll, Ingrid; Vulpen, Gertrud; Roldaan, Tim; Wagenaar, Wies; Boland, Melinde; Wolterbeek, Ron; Chavannes, Niels
Abstract Background Chronic obstructive pulmonary disease (COPD) exacerbations are associated with high disease burden and costs, especially in the case of hospitalizations. The overall number of hospital admissions due to exacerbations of COPD has increased. It is remarkable that re-admissions account for a substantial part of these hospitalizations. This pilot study investigates the use of case management to reduce re-admissions due to COPD. Methods COPD patients with more than one hospitalization per year due to an exacerbation were included. The participants (n = 10) were closely monitored and intensively coached for 20 weeks after hospitalization. The case manager provided care in a person-focused manner. The case manager informed and supported the patient, took action when relapse threatened, coordinated and connected primary and secondary care. Data of 12 months before and after start of the intervention were compared. Primary outcome was the difference in number of hospitalizations. Secondary outcomes were health-related quality of life (measured by the Clinical COPD Questionnaire, CCQ) and dyspnoea (measured by the MRC Dyspnoea Scale). Results The incidence rate of hospitalizations was found to be 2.25 times higher (95% confidence interval [CI] 1.3–3.9;P  = 0.004) 12 months before compared with 12 months after the start of case management. COPD patients had a mean CCQ score of 3.3 (95% CI 2.8–3.8) before and 2.4 (95% CI 1.9–2.8) after 20 weeks of case management; a difference of 1.0 (95% CI 0.4–1.6;P  = 0.001). The mean MRC scores showed no significant differences before (4.3; 95% CI 3.7–4.9) and after the case management period (3.9; 95% CI 3.2–4.6); a difference of 0.4 (95% CI − 0.1 to 0.9;P  = 0.114). Conclusions This pilot study shows that the number of COPD hospital re-admissions decreased significantly after the introduction of a case manager. Moreover, there was an improvement in patient-reported health-related quality of life.